PENGARUH MANFAAT DAN KEMUDAHAN E-FILLING TERHADAP PENYAMPAIAN SPT TAHUNAN WAJIB PAJAK ORANG PRIBADI PADA UPT LAPAS KELAS IIA TANJUNG RAJA - S Sahila; Kusminaini Armin (Fakultas Ekonomi Universitas Tridinanti Palembang, 2020)
The Directorate General of Taxes modernizes tax administration as a form of improving the quality of tax services for taxpayers, one of which is the development of tax reporting using electronic filling (e-Fillig). This study aims to determine the effect simultaneously and partially of the benefits and convenience of e-Fillling on the submission of annual tax returns for individual taxpayers.Based on multiple linear regression analysis, there is a simultaneous influence between the benefits of e-filling and the ease of e-filling on the submission of the annual tax return for individual taxpayers. Judging from the significance value (0.000 <0.05), it means that H0 is rejected and H1 is accepted. The results of the research are partially between the benefits and ease of e-Filling on the submission of the annual tax return for individual taxpayers, namely for the variable the benefits of e-Filling have a significant effect (0.000 <0.05) meaning that H0 is rejected and H1 is accepted, and for the e-Filing convenience variable has an effect. significant (0.000 <0.05) which means that H0 is rejected H1 is accepted.Keywords: Benefits of E-Filling, Ease of E-Filling, Submission of Annual Tax Return of Individual Taxpayers